Measurement of the Level of Health and Financial Performance Aspects in KUD Karangploso Savings and Loans Cooperative Units According to Juknis 15 of 2021 Concerning Cooperative Health Examinations - Sinta Idani Pertiwi; Irfan Fatoni; Dwi Anggarani; Indah Dewi Nurhayati (Optima Science, 2024)
This research aims to determine the measurement of the health level of financial performance aspects in the KUD Karangploso cooperative savings and loans units in accordance with technical guidelines 15 of 2021 concerning cooperative health inspections. The population in this study was the head, treasurer and secretary of KUD Karangploso (savings and loans units). The data collection method used in this research is by documentation, data obtained by viewing, recording, analyzing and evaluating data that has been documented by the KUD Karangploso savings and loans units where the data is data that is related and needed for research data sources. The results of this research show that the aspect of profitability and independence, in 2021 to 2022 received a maximum total score of 12, this shows that in that year the cooperative was able to at least maintain good financial performance including asset management, own capital and independence in managing operational expenses. cooperative. In terms of growth, from 2021 to 2022, the maximum total score was 16, this shows that in that year the cooperative was able to at least maintain a stable growth rate in asset management, funds received, equity and net business results.